RISKS FOR CANCER SCREENING IN PRIMARY CARE - Russell-Ladd, Katherine (My University, 2019)
Background: While numerous task force recommendations are in place, cancer still remains a major global health problem. Gaps in modern screening methods for cancer were noted among patients in primary care. Accessing information from patients can enable appropriate screening tests to occur, and prevent or discover malignant tissues in earlier stages. Methods: A quality improvement project was designed to develop a cancer screening questionnaire tool for use in primary care. The questionnaire was distributed to patients in a primary care clinic in Southeastern North Carolina. Use of the questionnaire enabled a more comprehensive approach to screening patients for cancer. Accompanying algorithm sheets were available to the provider to assist in interpreting the screening results based on guidelines. Results: Of the fifty patient visits to the primary care office, all patients were participants. Eight of those fifty were referred for more advanced screening. Conclusions: This project determined that employing an inclusive process for cancer screening resulted in a more comprehensive screening approach.
Keywords: Cancer, cancer screening in primary care, colorectal cancer, breast cancer, lung cancer, cervical cancer.